2011
DOI: 10.1124/jpet.110.177824
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Regulator Marizomib (NPI-0052) Exhibits Prolonged Inhibition, Attenuated Efflux, and Greater Cytotoxicity than Its Reversible Analogs

Abstract: The present study was undertaken to compare the cellular transport characteristics of [ 3 H]NPI-0052 (1R,4R,5S)-4-(2-.0]heptane-3,7-dione in RPMI 8226 multiple myeloma and PC-3 prostate adenocarcinoma cells to determine whether these properties explain differences in the cytotoxic potencies of these chemical analogs. The results indicate that marizomib, which possesses a chemicalleaving group, is more cytotoxic to both cell lines and inhibits proteasome activity more completely at lower concentrations than NPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Preclinical assays revealed that the irreversible binding of marizomib to the proteasome is responsible for its slower efflux, longer duration of action and greater cytotoxicity compared with other reversible analogs of bortezomib [100]. Stable disease was observed in patients with colorectal and hepatocellular carcinoma and also other tumor types, in a Phase I trial conducted in hematological and solid tumors [101].…”
Section: Targeting the Proteasomementioning
confidence: 99%
“…Preclinical assays revealed that the irreversible binding of marizomib to the proteasome is responsible for its slower efflux, longer duration of action and greater cytotoxicity compared with other reversible analogs of bortezomib [100]. Stable disease was observed in patients with colorectal and hepatocellular carcinoma and also other tumor types, in a Phase I trial conducted in hematological and solid tumors [101].…”
Section: Targeting the Proteasomementioning
confidence: 99%
“…Since carfilzomib displays differential binding properties compared to bortezomib it has been approved by the FDA for treatment of multiple myeloma patients that have previously received two prior therapies, including bortezomib and who subsequently relapsed. Marizomib (NPI-0052), a natural product derived from the fermentation of the marine actinobacterium Salinospora (Chauhan et al, 2005), also inhibits the chymotryptic-like activity of the 20S proteasome via a similar mechanism of action to bortezomib and carfilzomib (Herndon et al, 2013;Obaidat et al, 2011;Singh et al, 2010).…”
Section: Targeting the Ups In Cancermentioning
confidence: 99%
“…14 It is able to induce apoptosis in primary myeloma cells refractory to treatment with conventional myeloma therapies 73 and combines synergistically with bortezomib and lenalidomide in vivo. [74][75][76] ONX0912 is the only irreversible proteasome inhibitor that is orally bioavailable. It too has shown activity in myeloma cells resistant to conventional therapy and enhances tumor regression in vivo.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…[74][75][76] ONX0912 is the only irreversible proteasome inhibitor that is orally bioavailable. It too has shown activity in myeloma cells resistant to conventional therapy and enhances tumor regression in vivo.…”
mentioning
confidence: 99%